Egg incubation : - Deeming, D. Charles (Cambridge University Press, 2004)
This book reviews comprehensively incubation effects on embryonic development in birds and reptiles and presents the first ever synthesis of data from these two vertebrate classes. International experts in each field have contributed to this extensively referenced volume and it will be of great interest not only to research biologists, but also to bird and reptile breeders.